Effect of Fe3O4‐doped sepiolite on the flammability and thermal degradation properties of epoxy composites†. (26th November 2015) - Liu, Yun; Kong, Qing‐Hong; Zhao, Xiao‐Min; Zhu, Ping; Zhao, Jianqing; Esteban‐Cubillo, Antonio; Santarén, Julio; Wang, De‐Yi
Abstract : As‐received sepiolite/epoxy systems and Fe3 O4 ‐doped sepiolite/epoxy systems were prepared, and the contents of sepiolite and Fe3 O4 ‐doped sepiolite were kept as 2 and 4 wt%, respectively. Compared with sepiolite, the effect of Fe3 O4 ‐doped sepiolite on the flame retardancy, combustion properties, thermal degradation, thermal degradation kinetics and thermomechanical properties of epoxy resin was investigated systematically by limiting oxygen index (LOI), cone calorimeter (Cone), thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA). Some interesting results had been acquired. The addition of sepiolite decreased heat release rate, total smoke production and smoke production rate, and obviously improved LOI values of epoxy composites. Compared with sepiolite, the addition of Fe3 O4 ‐doped sepiolite further reduced parameters mentioned above of epoxy composites, and further enhanced LOI values and char residues after cone test. There might be a synergistic effect between sepiolite and Fe3 O4 on flame retardant epoxy composite. TGA results indicated that the addition of sepiolite had a slight effect on the thermal degradation of epoxy composites; however, the addition of Fe3 O4 ‐doped sepiolite accelerated the thermal degradation of epoxy composites. DMA results showed that the addition of both sepiolite and Fe3 O4 ‐doped sepiolite increased the glass transition temperature ( Tg ) of epoxy composite. The results obtained in this paper supplied an effective solution for developing excellent flame retardant properties of polymeric materials. Copyright © 2015 John Wiley & Sons, Ltd.